Image Processing Applications of Pulse Coupled Neural Networks - R, Mugunthan S (Journal of Innovative Image Processing, 2023)
The Pulse Coupled Neural Network (PCNN) is a neural network model that, when stimulated with a grayscale or colour image, generates binary pulse image collection. PCNN differs from other methods in several ways. It is unique due to its synchronous pulsed output, movable threshold, and programmable parameters. This research work reviews the current developments of PCNN and its applications in medical image processing domain. This study discusses the pulse coupled neural networks along with its application in various fields. Then, a summary of some current issues is presented along with some ideas to resolve it.
Keywords: Pulse Coupled Neural Network (PCNN); Medical Image processing; Neural Networks